2022
DOI: 10.1371/journal.pgen.1010314
|View full text |Cite
|
Sign up to set email alerts
|

A pals-25 gain-of-function allele triggers systemic resistance against natural pathogens of C. elegans

Abstract: Regulation of immunity throughout an organism is critical for host defense. Previous studies in the nematode Caenorhabditis elegans have described an “ON/OFF” immune switch comprised of the antagonistic paralogs PALS-25 and PALS-22, which regulate resistance against intestinal and epidermal pathogens. Here, we identify and characterize a PALS-25 gain-of-function mutant protein with a premature stop (Q293*), which we find is freed from physical repression by its negative regulator, the PALS-22 protein. PALS-25(… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 66 publications
2
31
0
Order By: Relevance
“…Instead, we harvested a population of animals with the average stage of L4 that also contained some older and younger animals. In differential expression analysis of our RNA-seq data, we found that 3,001 genes were upregulated in pals-17 mutants compared to wild-type animals, which significantly overlap with previously defined IPR genes (70/80 IPR genes) and genes upregulated in pals-22(jy3) mutants (262/457) (5) (Fig 4A, S1, S3 and S4 Tables). However, many of the differentially expressed genes in pals-17 mutants could be due to the wide range of developmental ages found in a population of these mutants (S3 Fig).…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…Instead, we harvested a population of animals with the average stage of L4 that also contained some older and younger animals. In differential expression analysis of our RNA-seq data, we found that 3,001 genes were upregulated in pals-17 mutants compared to wild-type animals, which significantly overlap with previously defined IPR genes (70/80 IPR genes) and genes upregulated in pals-22(jy3) mutants (262/457) (5) (Fig 4A, S1, S3 and S4 Tables). However, many of the differentially expressed genes in pals-17 mutants could be due to the wide range of developmental ages found in a population of these mutants (S3 Fig).…”
Section: Resultssupporting
confidence: 72%
“…All previously described triggers require ZIP-1 for induction of the pals-5p::GFP reporter. Here, we found that pals-17 RNAi induces expression of ZIP-1::GFP in intestinal nuclei (Fig S1), which also occurs in response to several other IPR triggers (5,14).…”
Section: Results Pals-17 Is a Negative Regulator Of The Ipr And An Es...mentioning
confidence: 64%
See 3 more Smart Citations